Inflection Points on Groundwater Age and Geochemical Profiles Along Wellbores Light up Hierarchically Nested Flow Systems. Issue 16 (23rd August 2021) - Zhang, Jun; Wang, Xu‐Sheng; Yin, Lihe; Wang, Wenke; Love, Andrew; Lu, Zheng‐Tian; Jiang, Wei; Yang, Guo‐Min; Xie, Yueqing; Wang, Xiaoyong; Sun, Fangqiang; Tang, Xiaoping; et al.
Abstract: Hierarchically nested groundwater flow systems have been widely investigated by numerical modeling and laboratory experiments but seldom recognized from in situ observations and testing. Groundwater age and geochemical profiles were obtained by the authors using a packer system along two wellbores drilled in the Ordos Plateau, China. Groundwater age profiles were constructed from 3 H, 85 Kr, 14 C, and 81 Kr data, with the apparent age generally increasing with depth, while exhibiting several inflection points. These inflection points were compared with geochemical profiles and numerical modeling results to delineate groundwater flow systems. Inflection points with significant increases in the gradients of age and Cl − concentration versus depth may indicate interfaces among flow systems. A concurrent decrease‐increase turning of groundwater age and Cl − concentration is influenced by a stagnation point. The groundwater age profiles are quite different from previous studies, indicating that the method can greatly reduce the uncertainty in model construction. Plain Language Summary: The provision of renewable groundwater, a crucial source of drinking water worldwide, relies on a circulation path from recharge to discharge zones with a subsurface flow in reservoirs (aquifers). Basin‐scale groundwater circulation is speculated to form hierarchically nested flow systems with differing capabilities for renewal. However, flow systems are invisible and difficult to detect through in situ observations on groundwater. In this study, nested groundwater flow systems were identified from groundwater age and geochemical profiles along wellbores. Inflection points on these profiles provide significant insights into the interfaces and stagnation points among nested groundwater flow systems. Uncertainties could be brought by the aquifer heterogeneity in the hydraulic conductivity and localized soluble salts. This adopted method is expected to be improved by incorporating geophysical survey and high‐resolution geochemical analyses to eliminate uncertainties in model construction. Key Points: Groundwater age and geochemical profiles were obtained to investigate groundwater flow systems Inflection points on profiles are used to infer interfaces or stagnation points among different groundwater flow systems Groundwater flow models constrained by inflection points greatly reduce the uncertainty of flow system characterization